Penerapan Teknologi Secara Terpadu dari Pemanfaatan Sampah di Kelompok Usaha Pengelolaan Sampah di Desa Sunggumanai - Muhammad Wiharto; Muhammad Anwar; Muhammad Arief Nasutions; Mohammad Wijaya.M; Muhammad Yunus (Universitas 45 Surabaya, 2025)
Currently, the management of abundant natural resources has not been managed optimally, even though if managed by the village community it becomes an opportunity of high economic value. Sunggumanai Village, Pattalasaang District, Gowa Regency consists of agricultural and plantation land. Rice fields consist of several rice fields, horticultural crops, the population of Sunggumanai Village is 2171 people consisting of 902 men and 1269 women with a total of 265 Heads of Families (KK). The Waste Management Business Group (KUPAS) is located in Japing Hamlet, Sunggumanai Village, Gowa Regency, which is one of the land areas with a lot of scattered waste, especially plastic and organic waste in South Sulawesi Province]. Sunggumanai Village to manage plastic waste into chopped plastic in the Village. This business belongs to a business group that was founded in 2023. Currently chaired by Mr. H. Rusli Mishaf, The purpose of implementing this PKM is to provide training and assistance in 1) Increasing knowledge and skills in making gasoline. 2) Introduction of new organic waste charcoal briquettes products to the market. 3) Improvement of charcoal briquettes and organic waste liquid smoke processing techniques through integrated pyrolysis technology. 5) Marketing of charcoal briquettes, organic waste liquid smoke, and compost products based on digital marketing. This relates to the SDGs, namely clean energy utilizing organic waste, and Affordable Climate Change Management by the PKM team.